Basement membranes in obstructive pulmonary diseases - Bart G.J. Dekkers (Elsevier, 2021)
Increased and changed deposition of extracellular matrix proteins is a key feature of airway wall remodeling in obstructive pulmonary diseases, including asthma and chronic obstructive pulmonary disease. Studies have highlighted that the deposition of various basement membrane proteins in the lung tissue is altered and that these changes reflect tissue compartment specificity. Inflammatory responses in both diseases may result in the deregulation of production and degradation of these proteins. In addition to their role in tissue development and integrity, emerging evidence indicates that basement membrane proteins also actively modulate cellular processes in obstructive airway diseases, contributing to disease development, progression and maintenance. In this review, we summarize the changes in basement membrane composition in airway remodeling in obstructive airway diseases and explore their potential application as innovative targets for treatment development.